2003
DOI: 10.1078/0944-5013-00178
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of chromium by the yeast Pichia guilliermondii: toxicity and accumulation of Cr (III) and Cr (VI) and the influence of riboflavin on Cr tolerance

Abstract: A comparative study has been made on the sensitivity of the yeast Pichia guilliermondii to Cr (III) and Cr (VI) as well as on the Cr uptake potential at growth-inhibitory concentrations of chromium. The strains used in the study were either isolated from natural sources or obtained from a laboratory strain collection. The results show that most of the natural strains were more tolerant to chromium and were able to grow in the presence of 5 mM Cr (III) or 0.5 mM Cr (VI), that is at concentrations which substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 40 publications
1
24
0
1
Order By: Relevance
“…It is likely that A. parasiticus may have taken up so much Cr(VI) that it could not convert to Cr(III) since intracellular accumulation of Cr(VI) may also disturb the normal functioning of microbial cells [34]. In studies of chromium toxicity and accumulation, Kshminska et al [10] reported diverse, individual and complex mechanism of chromium bioremediation in the cells of different strains of the yeast Pichia guilliermondii. They observed that all the investigated strains responded to Cr(VI) treatment with substantial changes in protein profile patterns, which included both induction and suppression of certain polypeptides.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is likely that A. parasiticus may have taken up so much Cr(VI) that it could not convert to Cr(III) since intracellular accumulation of Cr(VI) may also disturb the normal functioning of microbial cells [34]. In studies of chromium toxicity and accumulation, Kshminska et al [10] reported diverse, individual and complex mechanism of chromium bioremediation in the cells of different strains of the yeast Pichia guilliermondii. They observed that all the investigated strains responded to Cr(VI) treatment with substantial changes in protein profile patterns, which included both induction and suppression of certain polypeptides.…”
Section: Resultsmentioning
confidence: 99%
“…For the determination of total chromium uptake by the fungi, the mycelia were acid digested [10,32]. The cells were separated from the culture media by filtration, washed with water and dried.…”
Section: Determination Of Total Chromium Uptake By Fungal Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell-free extract was submitted at 95°C and tested for chromate reduction, but no changes were observed, which demonstrates that one type of enzyme should be conducting the reduction process. Additional studies conducted on C. maltosa (Ramírez et al 2004), Pichia jadinii (Ksheminska et al 2003) and Aspergillus tubingensis Ed8 (Coreno et al 2009) have demonstrated the high specific activity of chromate reductase in crude extract, but not in the membrane fraction.…”
Section: Direct Reductionmentioning
confidence: 99%